Electrodeposition of brass from polyligand electrolyte based on pyrophosphate - Serhiienko, Olena; Artemenko, Valentina; Rutkovska, Katerina; Maizelis, Antonina (Фізико-механічний інститут ім. Г. В. Карпенко, 2019)
The purpose of the research is to determine the conditions for brass electrodeposition from a polyligand electrolyte containing pyrophosphate and citrate metal complexes. Methods of cyclic voltammetry and galvanostatic deposition were used. It is determined the region of current densities, in which the current efficiency is the highest, the deposit is more uniform in the thickness, and alloy composition is practically unchanged.